2021
DOI: 10.3390/ijerph18179111
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease and Chronic Endodontic Infection. Is There an Association? A Systematic Review and Meta-Analysis

Abstract: The aim of the present study was to systematically assess existing evidence on the possible association between chronic endodontic infections and cardiovascular disease (CVD). An electronic database search was implemented until 2 October 2020. The main outcome was risk of CVD diagnosis. Risk of bias was assessed through the ROBINS-I tool, while random effects meta-analyses were conducted. The quality of the evidence was assessed with the Grading of Recommendations Assessment, Development, and Evaluation. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…As a result, it was observed that the risk of CVD diagnosis in patients with chronic endodontic infection was 1.38 times those without infection. Therefore, there are indications for an identified association between chronic endodontic infection and CVD [19].…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it was observed that the risk of CVD diagnosis in patients with chronic endodontic infection was 1.38 times those without infection. Therefore, there are indications for an identified association between chronic endodontic infection and CVD [19].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is key to determine the risk factors associated with CVD. The relationship between AP and cVd has been investigated for several decades and numerous reviews or meta-analyses have been published (186)(187)(188)(189). Most studies have found a weak correlation between AP and cVd (186)(187)(188)(189)(190)(191), with only a few disagree (192,193).…”
Section: Cvdmentioning
confidence: 99%
“…The relationship between AP and cVd has been investigated for several decades and numerous reviews or meta-analyses have been published (186)(187)(188)(189). Most studies have found a weak correlation between AP and cVd (186)(187)(188)(189)(190)(191), with only a few disagree (192,193).…”
Section: Cvdmentioning
confidence: 99%
“…In addition, long-term consequences of oral diseases and tooth loss tend to further influence other mechanisms in the entire body regarding systemic health (e.g., weight loss, diabetes, cardiovascular diseases, dementia, Alzheimer's disease, and spatial cognitive impairment). 5,[7][8][9][10][11] Therefore, a huge amount of effort must be put to develop biomaterials by sorting out oral health problems faced in dentistry. The selection of biomaterials is being done considering the end product's potential physical, chemical, and biological characteristics.…”
Section: Introductionmentioning
confidence: 99%